Infections caused by Tissierella praeacuta: A report of two cases and literature review. (August 2016) - Caméléna, F.; Pilmis, B.; Mollo, B.; Hadj, A.; Le Monnier, A.; Mizrahi, A.
Abstract: Herein we report two cases of infections caused by Tissierella praeacuta and a review of the literature. The first case was a septic pseudarthrosis of the left femur after multiple fractures. Two per-operative samples were positive with T. praeacuta . The patient was successfully treated by piperacillin – tazobactam and metronidazole. The second case was a bacteremia in a patient suffering from pyonephrosis and a hepatic abscess. The treatment was meropenem. No relapses were observed in both cases. Identification of the strains using MALDI-TOF coupled to mass spectrometry (MS) (Beckman coulter, France) was inconclusive in the two cases. Identification by 16S rRNA sequencing was then performed. This bacterium was susceptible to beta-lactams, chloramphenicol, rifampicine and metronidazole. Highlights: First case of prosthetic knee joint infection by Tissierella praeacuta . Blood stream infection caused by Tissierella praeacuta . Literature review of infections caused by Tissierella praeacuta . 16S rRNA sequencing of Tissierella praeacuta .